Records of the Colony and Plantation of New Haven: From 1638 To 1649, at 131-32 (Charles J. Hoadly ed., 1857) (enacted 1644) - (:unkn) unknown (My University, 1644)
One quarter of each plantation's militia will attend church services with "arms compleat" with five to six charges of powder, firelocks, and shot. Penalty of two shillings for neglect and one shilling for late arrival.
Keywords: REQUIRED POSSESSION